Regionalitet og sproglig kontakt i vikingetid og middelalder: Strofer om silke og ærlig pæl - Gammeltoft, Peder; Holck, Jakob Povl (Hikuin, 2008)
Regionality and language contact during the Viking Age and the Middle Ages By Peder Gammeltoft and Jakob Povl Holck This article is a comparative analysis of two important influences on Southern Scandinavia during the Viking Age and the early Middle Ages, namely the Anglo-Saxon and the Slavic (Wendish) cultures. The historical and archaeological evidence for these two influences are well known and established beyond doubt. But how do these influences manifest themselves in the linguistic landscape in Southern Scandinavia – are they regional in character, or even supra-regional? By paying careful attention to the linguistic differences between Scandinavian and Old English/Wendish, it is possible to establish a number of criteria by which it is possible to determine the origin of a word. The result of the analysis is that Old English has left a relatively large number of traces in the Scandinavian word stock, whereas Wendish is almost absent. By integrating place-names of Old English and Wendish origin into the survey, it is possible to modify this picture somewhat. The influence from Old English is mainly connected to learning and Christianity and to some extent to the sphere of nobility, seemingly spurred by a relatively high degree of bilingualism. The Wendish influence, on the other hand, seems to be related to a limited, but relatively concentrated settlement in Lolland, Falster and Møn in Denmark and to trade. The status of the Wendish language was however not very high, whereas Old English – being to a great extent associated with the introduction of Christianity – appears to have been of high status. The close linguistic relationship of Scandinavian with Old English may also have been a contributing factor.